High serum IL-6 correlates with reduced clinical benefit of atezolizumab and bevacizumab in unresectable hepatocellular carcinoma - Hannah Yang; Beodeul Kang; Yeonjung Ha; Sung Hwan Lee; Ilhwan Kim; Hyeyeong Kim; Won Suk Lee; Gwangil Kim; Sanghoon Jung; Sun Young Rha; Vincent E. Gaillard; Jaekyung Cheon; et al. (JHEP Reports, 2023)
Background & Aims: We elucidated the clinical and immunologic implications of serum IL-6 levels in patients with unresectable hepatocellular carcinoma (HCC) treated with atezolizumab and bevacizumab (Ate/Bev). Methods: We prospectively enrolled 165 patients with unresectable HCC (discovery cohort: 84 patients from three centres; validation cohort: 81 patients from one centre). Baseline blood samples were analysed using a flow cytometric bead array. The tumour immune microenvironment was analysed using RNA sequencing. Results: In the discovery cohort, clinical benefit 6 months (CB6m) was defined as complete or partial response, or stable disease for ≥6 months. Among various blood-based biomarkers, serum IL-6 levels were significantly higher in participants without CB6m than in those with CB6m (mean 11.56 vs. 5.05 pg/ml, p = 0.02). Using maximally selected rank statistics, the optimal cut-off value for high IL-6 was determined as 18.49 pg/ml, and 15.2% of participants were found to have high IL-6 levels at baseline. In both the discovery and validation cohorts, participants with high baseline IL-6 levels had a reduced response rate and worse progression-free and overall survival after Ate/Bev treatment compared with those with low baseline IL-6 levels. In multivariable Cox regression analysis, the clinical implications of high IL-6 levels persisted, even after adjusting for various confounding factors. Participants with high IL-6 levels showed reduced interferon-γ and tumour necrosis factor-α secretion from CD8+ T cells. Moreover, excess IL-6 suppressed cytokine production and proliferation of CD8+ T cells. Finally, participants with high IL-6 levels exhibited a non-T-cell-inflamed immunosuppressive tumour microenvironment. Conclusions: High baseline IL-6 levels can be associated with poor clinical outcomes and impaired T-cell function in patients with unresectable HCC after Ate/Bev treatment. Impact and implications: Although patients with hepatocellular carcinoma who respond to treatment with atezolizumab and bevacizumab exhibit favourable clinical outcomes, a fraction of these still experience primary resistance. We found that high baseline serum levels of IL-6 correlate with poor clinical outcomes and impaired T-cell response in patients with hepatocellular carcinoma treated with atezolizumab and bevacizumab.